Influence Ratio of Pineapple with Papaya and Arabic Gum Concentration on The Quality of Fruit Leather - Mei Sya Putri Lubis; Rona J Nainggolan; Era Yusraini (Universitas Sumatera Utara, 2014)
The aim of this research was to find the effect of ratio pineapple with papaya pulps and several arabic gum concentration on the quality of pineapple and papaya of mixture fruit leather. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e. :ratio of pineapple with papaya pulps (P) : (65% : 35% ; 60% : 40% ; 55% : 45% ; 50% : 50%) and arabic gum concentration (K): (0,6%, 0,8%, 1% and 1,2%). Parameters analyzed were moisture content, ash content, vitamin C content, curb fiber content, total soluble solid, total acid, pH, score organoleptic values of colour, taste and texture and hedonic organoleptic values of colour, taste, flavour and texture. The results showed that ratio pineapple with papaya pulps provide highly significant effect on moisture content, ash content, vitamin C content, curb fiber content, total soluble solid, total acid, pH, score organoleptic values of colour, taste and texture, and hedonic organoleptic values of colour, flavor, taste and texture. Arabic gum concentration had highly significant effect on moisture content, vitamin C content, curb fiber content, total soluble solid, total acid, score organoleptic values of colour, taste and texture, and hedonic organoleptic values of texture. Interactions of the two factors had highly significant effect on moisture content, and had no significant effect on ash content, vitamin C content, curb fiber content, total solubility solid, total acid, pH, score organoleptic values of colour, taste and texture, and hedonic organoleptic values of colour, flavor, taste and texture. The ratio of pineapple with papaya pulps of (50% : 50%) and arabic gum concentration of (1,2%) produced the best quality of fruit leather and more acceptable. Keywords : Arabic gum, Fruit leather, Papaya, Pineapple.